INTERACTIVE GAMES AND EXERCISES ON THE USE OF DIAGRAMS AND GRAPHS - Toshboyeva Saidakhon; Usmonova Sabohatkhon (Bright Mind Publishing, 2025)
This article describes measures aimed at the field of mathematics in Uzbekistan. It also reflects methods of explaining the topic of analyzing information based on diagrams and graphs and developing skills in primary school students. Information is provided on this topic on their role in the development of primary school students, improving their critical thinking, and logical analysis skills. In particular, several methods of interactive games and exercises on the use of diagrams and graphs, their effectiveness in use, and the relevance of teaching in primary school are discussed.
Keywords: Interactive games, diagrams, graphs, exercises, methods and techniques.